PWE-144 Frax Score in the Assessment of Bone Mineral Density Changes in Tenofovir Treated Chronic Hepatitis B Patients. (4th June 2013) - Gill, U S; Zissimopoulos, A; Al-shamma, S; Burke, K; McPhail, M; Barr, D; Ross, V; Kallis, Y; Kooner, P; Marley, R; Foster, G R; Kennedy, P T
Abstract : Introduction: Tenofovir Disoproxil Fumarate (TDF) is an established oral antiviral (OAV) in the treatment of Chronic Hepatitis B (CHB). Bone Mineral Density (BMD) loss has been described in TDF treated HIV patients, but limited data exist in CHB. We have used DEXA scanning to determine BMD changes in TDF treated patients and have reported the possibility of BMD loss. DEXA scanning, however, is costly and requires longitudinal follow-up. We assessed the value of the FRAX® score and of bone biochemistry to evaluate their utility in TDF treated patients. Methods: The FRAX score is a WHO web-based tool, used to calculate 10-year fracture risk and the need for lifestyle modification, DEXA scanning or preventative treatment. CHB patients treated with TDF for a minimum of 12-months and a control group not exposed to TDF were studied. 122 TDF exposed patients (male = 89), median age 45 (range = 26–64) and 48 patients (male = 31), median age 36 (range = 20–62) not exposed to TDF were DEXA scanned and included in the study. We calculated FRAX scores and recorded bone biochemical markers, comprising serum Alkaline Phosphatase (sALP), Calcium (sCa) and Phosphate (sPO). Results: TDF treated patients had lower hip T-scores compared to controls (p = 0.02). On univariate analysis factors associated with a hip T-score < 1 included older age, lower BMI, smoking and TDF exposure (p = < 0.05). On multivariate analysis the same factors were associated with a hip T-score < 1, but TDF lost significance. For the development of a major osteoporotic fracture the pre-DEXA FRAX score was 4.77% compared to 4.33% (post-DEXA FRAX) (p = 0.9) and for a hip fracture this was 0.54% (pre-DEXA FRAX) and 0.77% (post-DEXA FRAX) (p = 0.5). The pre-DEXA FRAX score was a significant predictor of the post-DEXA FRAX treatment recommendation (p = < 0.001). TDF therapy was associated with increased sALP after 12-months, but this was not significant. No change was observed in pre-treatment sCa and sPO levels compared to those after 12-months exposure (p = 0.5 & 0.09 respectively). Conclusion: Our results demonstrate the FRAX score alone can accurately predict the risk of developing an osteoporotic fracture in TDF treated CHB patients. This potentially obviates the need for DEXA scanning and the associated costs. The relationship between sALP and TDF is noteworthy, but bone parameters are of limited use in predicting BMD changes. Although BMD loss in TDF treated CHB patients remains unproven, we demonstrate the use of the FRAX score may determine those at risk of osteoporotic fractures in CHB. Disclosure of Interest: None Declared.